The role of conserved charged residues in the bidirectional rotation of the bacterial flagellar motor. Issue 4 (24th March 2018) - Onoue, Yasuhiro; Takekawa, Norihiro; Nishikino, Tatsuro; Kojima, Seiji; Homma, Michio
Abstract: Many bacteria rotate their flagella both counterclockwise (CCW) and clockwise (CW) to achieve swimming toward attractants or away from repellents. Highly conserved charged residues are important for that motility, which suggests that electrostatic interactions are crucial for the rotor–stator function. It remains unclear if those residues contribute equally to rotation in the CCW and CW directions. To address this uncertainty, in this study, we expressed chimeric rotors and stators from Vibrio alginolyticus and Escherichia coli in E. coli, and measured the rotational speed of each motor in both directions using a tethered‐cell assay. In wild‐type cells, the rotational speeds in both directions were equal, as demonstrated previously. Some charge‐neutralizing residue replacements in the stator decreased the rotational speed in both directions to the same extent. However, mutations in two charged residues in the rotor decreased the rotational speed only in the CCW direction. Subsequent analysis and previous results suggest that these amino acid residues are involved in supporting the conformation of the rotor, which is important for proper torque generation in the CCW direction. Abstract : Highly conserved charged residues are involved in the rotor‐stator interaction in the bidirectional rotary motor of bacterial flagella. We found that the wild‐type motor produces the same torque in both directions but some mutants of these residues in the rotor produce less torque in one rotational direction. We suggest that these amino acid residues are involved in supporting the conformation of the rotor.